“Just a Swinging Door” – Examining the Egocentric Misconception of Meditation - Saari, Antti Wiljami; Pulkki, Jani (Paideusis, 2012)
Various kinds of contemplative practices have been a part of the western philosophical tradition since the Age of Antiquity. Today, however, philosophy as a way of life has ceased to be an integral part of academic practice. The capability to gain knowledge or understanding is believed to come out of pure intellectual endeavor, without exercising the mind and body holistically. This has created a blind spot for philosophy, where no profound pedagogical and moral transformation of subjectivity can be articulated. Furthermore, meditation practices have often been understood as egoistic, apolitical activity. Our purpose is to suggest that this understanding is due to the liberalist and Cartesian tradition of subjectivity today widely proliferated in education. However, through an analysis of a meditation exercise in breathing, it is possible to deconstruct these notions and open novel vistas for thinking about the relationship between truth and subjectivity in education. A simple breathing exercise can dissolve the dualisms ingrained in occidental philosophy and culture - which has many socio-political implications for educational theory and praxis